1996
DOI: 10.2307/3433157
|View full text |Cite
|
Sign up to set email alerts
|

Phenylguanine Found in Urine after Benzene Exposure

Abstract: Comparative investigations with synthetic N7-phenylguanine were carried out to clarify whether this compound is eliminated via the urine of rats as a benzene-derived nucleic acid adduct. As sensitive methods for detecting trace amounts of the compound, gas chromatography-mass spectroscopy, high performance liquid chromatography, and two immunoassays (enzyme-linked immunosorbent assay and fluoroimmunoassay) with appropriate monoclonal antibodies were used. The results indicate the excretion of several benzene-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…When Norpoth et al detected in urine of rats dosed with benzene a compound co-eluting with and showing similar UV spectrum as authentic 7-phenylguanine (7-PhG), it seemed that 7-PhG could find application as a molecular dosimeter of both exposure and DNA damage by benzene (Norpoth et al, 1988;Schell et al, 1993). However, this finding was later disproved by the same group, when urinary 7-PhG could not be confirmed by more sensitive methods, such as ELISA and FIA using specific monoclonal antibodies (Norpoth et al, 1996). The authors concluded that compound(s) slightly different from 7-PhG, possibly containing a hydroxy function, were excreted as guanine adduct(s) of benzene (Schell et al, 1993).…”
Section: Introductionmentioning
confidence: 92%
“…When Norpoth et al detected in urine of rats dosed with benzene a compound co-eluting with and showing similar UV spectrum as authentic 7-phenylguanine (7-PhG), it seemed that 7-PhG could find application as a molecular dosimeter of both exposure and DNA damage by benzene (Norpoth et al, 1988;Schell et al, 1993). However, this finding was later disproved by the same group, when urinary 7-PhG could not be confirmed by more sensitive methods, such as ELISA and FIA using specific monoclonal antibodies (Norpoth et al, 1996). The authors concluded that compound(s) slightly different from 7-PhG, possibly containing a hydroxy function, were excreted as guanine adduct(s) of benzene (Schell et al, 1993).…”
Section: Introductionmentioning
confidence: 92%
“…A N-7-fenilguanina pode ser determinada na urina por HPLC-UV após pré-tratamento da amostra empregando cromatografia de íons e extração em fase sólida. Apesar da determinação ser específica e estar diretamente ligada à carcinogenicidade do benzeno, a sensibilidade do método analítico não permite avaliações de exposição à concentrações inferiores à 5 ppm (16 mg.m -3 ) de benzeno no ar [44][45] . Nos últimos anos, os ácidos trans,trans-mucônico (AM) e S-fenilmercaptúrico (AFM) têm sido determinados na urina como IBEs.…”
Section: Figura 1 Esquema Do Metabolismo Do Benzenounclassified